Mr Nobody's eyes by - Morpurgo, Michael (Egmont, 2015)
Washed up on an island in the Pacific, Michael struggles to survive on his own. With no food and no water, he curls up to die. When he wakes, there is a plate beside him of fish, of fruit, and a bowl of fresh water. He is not alone...